Missed Opportunities for Vaccination in the Dominican Republic: Results of an Operational Investigation. (12th October 2016) - Garib, Zacarías; Vargas, Aida Lucía; Trumbo, Silas P.; Anthony, Kathleen; Diaz-Ortega, Jose Luis; Bravo-Alcántara, Pamela; Leal, Irene; Danovaro-Holliday, M. Carolina; Velandia-González, Martha
Abstract : Background . Despite the success of the Dominican Republic's National Immunization Program, homogenous vaccine coverage has not been achieved. In October 2012, the country implemented a study on missed opportunities for vaccination (MOVs) in children aged <5 years. Methods . A cross-sectional study of 102 healthcare facilities was implemented in 30 high-risk municipalities. Overall, 1500 parents and guardians of children aged <5 years were interviewed. A MOV is defined as when a person who is eligible for vaccination and with no contraindications visits a health facility and does not receive a required vaccine. We evaluated the causes of MOVs and identified risk factors associated with MOVs in the Dominican Republic. Results . Of the 514 children with available and reliable vaccination histories, 293 (57.0%) were undervaccinated after contact with a health provider. Undervaccinated children had 836 opportunities to receive a needed vaccine. Of these, 358 (42.8%) qualified as MOVs, with at least one MOV observed in 225 children (43.7%). Factors associated with MOVs included urban geographic area (OR = 1.80; p = 0.02 ), age 1–4 years (OR = 3.63; p ≤ 0.0001 ), and the purpose of the health visit being a sick visit (OR = 1.65; p = 0.02 ). Conclusions . MOVs were associated primarily with health workers failing to request and review patients' immunization cards.